(untitled) (Journal of Medical & Health Sciences Review, 2025)
Counterfeit and substandard medicines pose significant public health challenges in low- and middle-income countries, including Pakistan. This study assessed the prevalence of falsified medicines and evaluated the operational integrity of the pharmaceutical supply chain. A mixed-methods approach was employed, integrating laboratory analysis of 180 medicine samples across antibiotics, cardiovascular drugs, and analgesics with qualitative interviews of 30 key stakeholders from regulatory authorities, manufacturers, distributors, and pharmacies. Laboratory results indicated that 20% of antibiotics, 13.3% of cardiovascular drugs, and 16.7% of analgesics failed quality standards, with falsified products detected in all categories. Informal retail outlets exhibited the highest failure rate (35%), highlighting vulnerabilities at the distribution level. Stakeholder insights revealed weak distributor verification, limited adoption of digital authentication technologies, and insufficient inspection and reporting mechanisms, which collectively enabled counterfeit infiltration. The study underscored the urgent need for regulatory strengthening, implementation of serialization and track-and-trace systems, capacity building for pharmacists and supply-chain personnel, and public awareness initiatives. Findings contribute to understanding systemic weaknesses in Pakistan’s pharmaceutical supply chain and provide actionable recommendations to enhance medicine quality and patient safety. Future research should focus on longitudinal monitoring of interventions, broader geographic coverage, and integration of innovative digital technologies to prevent counterfeit circulation.